PERAN PUSAT PELAYANAN TERPADU PEREMPUAN DAN ANAK DALAM PENDAMPINGAN ANAK-ANAK KORBAN KEKERASAN SEKSUAL BERMASALAH SOSIAL DI KABUPATEN WONOGIRI - Sella Kusumawati; Dzunuwanus Ghulam Manar; Kushandajani Kushandajani (Journal of Politic and Government Studies, 2015)
Sexual violence against children occurs in various places with various types of sexual violence. The majority of victims of sexual violence are children who have social problems example : poverty, children with disabilities and abandoned children who have no education and protection of the family is enough. Therefore, a program of social assistance is necessary. Wonogiri government show concern for child victims of sexual violence by launching Wonogiri Regulation 2 of 2013 on the implementation of the protection of victims of gender-based violence and child and continues to form an Integrated Services Center for Women and Children (P2TP2A) in 2013 as an intermediary between local government and child victims of sexual violence with social problem in a program of social assistance.This study aim is to know the origin Wonogiri local governments establish service centers Integrated Women and children as well as describe the performance of the programs Integrated Services Center for Women and Children on District Wonogiri to child victims of sexual violence with social problem. Data were collected through observation, interviews and related research. Qualitative data analysis techniques with analyzing in the form of description, depiction and conclusions on the object under study.From this research, it can be concluded that since forming Integrated Services Center for Women and Children assistance to child victims of sexual violence in Wonogiri social problems can be managed properly. Management program performance of assistance done by them already effective and sustainable as well as cooperation among agencies and civil society are evolving very helpful in improving the welfare of child victims of sexual abuse, although the lack of human resources from the Integrated Service Center of Women and children (P2TP2A) and lack of supervision of the Local Government in the performance of the related SKPD when doing assistance program an obstacle than an assistance program was established.Keywords : Child Social Welfare, Child Sexual Abuse, Sosial Assistance